Knockdown of Hypoxia-Inducible Factor 1α (HIF-1α) Promotes Autophagy and Inhibits Phosphatidylinositol 3-Kinase (PI3K)/AKT/Mammalian Target of Rapamycin (mTOR) Signaling Pathway in Ovarian Cancer Cells - Huang, Jinling (Med Sci Monit, 2019)
BACKGROUND: Ovarian cancer has the highest mortality rate among all female genital tumors because of its insidious onset and drug resistance. Hypoxia-inducible factor 1α (HIF-1α), one of the best-studied oncogenes, plays an important part in tumor adaptation to microenvironmental hypoxia and was found to be overexpressed in several malignancies, including ovarian cancer. Previous studies found that the effect of HIF-1α on cancers may be correlated with autophagy and some signaling pathways, such as PI3K/AKT/mTOR, in several tumors. However, the function and potential mechanism have not been clearly defined. MATERIAL/METHODS: The expression of HIF-1α in ovarian cancer tissues were detected by immunohistochemistry. HIF-1α was knocked down by siRNA transfection. Cell viability was examined by CCK8 and colony formation assay. Apoptosis and autophagy were detected with flow cytometry, transmission electron microscopy, and laser scanning confocal microscopy, respectively. The proteins related to autophagy and PI3K/AKT/mTOR were detected through Western blot analysis. RESULTS: HIF-1α was expressed at higher levels in epithelial or metastatic ovarian cancer tissue than in normal fallopian tube tissue. When HIF-1α was knocked down by siRNA in A2780 and SKOV3 cells, the viability of ovarian cancer cells was weakened, but the apoptosis and autophagy were strengthened. Accordingly, autophagosome formation increased and the expression of autophagy-related proteins LC3 and P62 increased in HIF-1α knockdown cells. The PI3K/Akt/mTOR signaling pathway was also found to be inactivated in HIF-1α knockdown cells. CONCLUSIONS: These findings show that knockdown of HIF-1α promoted autophagy and inhibited the PI3K/AKT/mTOR signaling pathway in ovarian cancer cells.